2006
DOI: 10.3352/jeehp.2006.3.3
|View full text |Cite
|
Sign up to set email alerts
|

The Future of e-Learning in Medical Education: Current Trend and Future Opportunity

Abstract: A wide range of e-learning modalities are widely integrated in medical education. However, some of the key questions related to the role of e-learning remain unanswered, such as (1) what is an effective approach to integrating technology into pre-clinical vs. clinical training?; (2) what evidence exists regarding the type and format of e-learning technology suitable for medical specialties and clinical settings?; (3) which design features are known to be effective in designing on-line patient simulation cases,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 17 publications
1
68
0
9
Order By: Relevance
“…Some institutions are using e-learning as a part of their blended curricula in which e-learning is playing a role of supplementing or as an adjunct tool (5) .…”
Section: Introductionmentioning
confidence: 99%
“…Some institutions are using e-learning as a part of their blended curricula in which e-learning is playing a role of supplementing or as an adjunct tool (5) .…”
Section: Introductionmentioning
confidence: 99%
“…The a-priori reluctance of our participants to incorporate e-learning in teaching, like that found in many other studies (e.g., Kim, 2006;Raby & Meunier, 2011;Tondeur et al, 2012), confirms the need for professional support to overcome these barriers. In light of the great potential of CoI as learning enhancers, our aim was to increase its utilization in medical courses, despite this widespread a-priori reluctance of medical educators to adopt it.…”
Section: Discussionmentioning
confidence: 54%
“…The effort spent on curriculum design and standardization may explain the frequently use of program competency variable [38]. Moreover, there are studies stating that academic achievement and skills are investigated frequently [34]. Besides, it was observed that such professional competencies as patient rights and responsibility of the doctor weren't investigated in the post-graduate level and barely investigated in the continuing education level.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of interview, questionnaire and observation form is expressed to be increasing because of the growing popularity of case studies as a research design in medical education researches [34]. The widely use of questionnaire and achievement tests may have required the descriptive or predictive analyses to be conducted in the researches frequently.…”
Section: Discussionmentioning
confidence: 99%